Cefixime and cefixime-clavulanate for screening and confirmation of extended-spectrum beta-lactamases in Escherichia coli - Mohammad Al-Tamimi; Hadeel Albalawi; Marwan Shalabi; Jumana Abu-Raideh; Ashraf I. Khasawneh; Farah Alhaj (BMC, 2022)
Abstract Introduction Detection of Extended-Spectrum Beta-Lactamases (ESBLs) depends on screening for resistance to certain cephalosporins, confirmation with selective ESBL inhibitors, and ESBL genes detection. New tests are required for accurate ESBL detection. Aims To test the ability of cefixime (CFM) and cefixime-amoxicillin/clavulanate (CFM-AMC) as a screening and confirmatory test for ESBL identification. Methods 246 clinical isolates of Escherichia coli were tested by an ESBL screening test, a double-disk synergy test (DDST), a disk replacement test, the Vitek 2 ESBL test, and an ESBL genes test by PCR. CFM ESBL Screening was performed by disk diffusion, while CFM-AMC confirmation was performed by DDST and a disk replacement test. Results 246 E. coli clinical isolates from two referral hospitals were collected over 2 years. The mean age ± standard deviation of patients was 43.8 ± 27.7 years and 76.8% were females. Resistance rates to penicillins, first, second, and third generation cephalosporins, and monobactams were very high at 97%, 84%, 100% and 97%, respectively. ESBL screening was positive in 81.3% of isolates, DDST was positive in 74.8%, disk replacement was positive in 79%, Vitek 2 ESBL test was positive in 67.3%, and ESBL genes were detected in 85.8% of isolates (CTX-M 75%, TEM 42.5%, SHV 4.6%). Compared to genotyping, screening with CFM achieved 87.7% sensitivity and 64.7% specificity. CFM-AMC DDST achieved 75.8% sensitivity and 75.4% specificity, and CFM-AMC disk replacement had 73% sensitivity and 70% specificity. Conclusions High prevalence of ESBLs was noted among E. coli isolates, dominated by CTX-M genotype. ESBL screening and confirmation using CFM and CFM-AMC is a new and accurate method for ESBLs detection.